Bio-efficacy of herbicides against different weed flora of wheat in central plain zone of Uttar Pradesh - Siddiqui, M.Z.; Yadav, R.A.; Khan, N.; Parihar, G.S.; Kumar, Arvind (Annals of Agricultural Research, 2016)
Wheat is the most widely cultivated crop among the cereals and ranks next to the rice in term ofproduction. Wheat crop incurred heavy loss due to weed infestation, the most dominant weeds inwheat crop are Phalaris minor, Chenopodium album, Melilotus alba, Anagallis arvensis and Convolvulusarvensis etc. About 37% yield losses occurs due to grass weeds only. Conventional method ofweed removal is costly as well as ineffective. Whereas, application of herbicides for controllingweeds have been found effective and economical in wheat crop. Results revealed that weedsprevailed through-out the crop period caused, on an average, yield reduction of 42%. Theapplication of herbicides viz. clodinafop-propargyl (15%) + metsulfuron (1%), sulfosulfourn (75%WG) + metsulfuron methly (5% WG) and clodinafop-propargyl 15% WP @100% recommendeddose (RDC) shows greater effect on control of Phalaris minor. clodinafop-propargyl (15%) +metsulfuron (1%) @ 100% RDC showed very effective against grasses as well as broadleaf weedsfollowed by SF-10 100% RDC and clodinafop-propargyl (15%) + metsulfuron (1%) @ 75% RDC,respectively. All the yield attributing character viz., spike weight (g), length of spike (cm), numberof spikelets/spike and 1000-grain weight were also maximized under clodinafop-propargyl (15%)+ metsulfuron (1%) (100% RDC) under herbicide application treatments. The weed free treatmentprovided maximum grain yield (50.06 q/ ha) followed by treatment where clodinafop-propargyl(15%) + metsulfuron (1%) (100% RDC) (49.13 q/ha) was applied.